Uncertainty, Threat, and the Role of the Media in Promoting the Dehumanization of Immigrants and Refugees. (9th September 2013) - Esses, Victoria M.; Medianu, Stelian; Lawson, Andrea S.
Abstract : Immigration policies and the treatment of immigrants and refugees are contentious issues involving uncertainty and unease. The media may take advantage of this uncertainty to create a crisis mentality in which immigrants and refugees are portrayed as "enemies at the gate" who are attempting to invade Western nations. Although it has been suggested that such depictions promote the dehumanization of immigrants and refugees, there has been little direct evidence for this claim. Our program of research addresses this gap by examining the effects of common media portrayals of immigrants and refugees on dehumanization and its consequences. These portrayals include depictions that suggest that immigrants spread infectious diseases, that refugee claimants are often bogus, and that terrorists may gain entry to western nations disguised as refugees. We conclude by discussing the implications of the findings for understanding how uncertainty may lead to dehumanization, and for establishing government policies and practices that counteract such effects.